Računalniška simulacija proizvodnje metanola iz različnih organskih energetskih surovin - Trop, Peter (visokošolska dela, 2015)
This doctoral dissertation presents two ideas regarding the uses of renewable raw materials for the production of methanol. The first idea deals with usage of biogas and natural gas mixtures within the existing plant for the production of methanol, which is based on the steam reforming. The compressor equipment was designed and the technology for the desulphurisation of the biogas chosen. An existing methanol plant that uses natural gas was modelled in Aspen Plus. In the next step the same model was used to simulate the production of methanol from a mixture of biogas and natural gas. Sensitivity analyses were performed by varying the ratio between biogas and natural gas. The results showed that replacing a part of the natural gas with biogas is reasonable, as evidenced by substantial savings and a relatively short payback period for the designed equipment. The second idea deals with the co-gasification of torrefied biomass and coal. Firstly simulation of the production of methanol from coal was modelled in Aspen Plus. Simulation includes the drying and gasification of coal, desulphurisation of synthesis gas, water-gas shift reaction, removal of CO2 from synthesis gas, and the production of methanol. Furthermore, the same model was used for the gasification of a mixture of torrefied biomass and coal with a ratio of 1:1 in relation to the heating value. Both processes were thermally integrated using Aspen Energy Analyser. The produced steam was then used within a simulated triple-stage steam turbine in order to produce electricity. Both processes were compared in terms of technological efficiency and economic feasibility using the net present value and internal return rate. The predicted prices were taken into account for the raw materials and products. Technological efficiency amounted to 70%, for the coal gasification case and 69.2%, for the co-gasification of biomass and coal respectively. It was shown that the coal-only case would perform slightly better in terms of economics than the co-gasification case. Sensitivity analyses showed that if the price of biomass were to decrease by 20% or the CO2 allowance price were to increase by 60%, both processes would be economically comparable.
Keywords: chemical engineering; computer simulations; Disertacije; economics; ekonomika; gasification; kemijsko inženirstvo; Metanol; methanol production; obnovljive surovine; Proizvodnja; proizvodnja metanola; računalniške simulacije; renewable raw materials; Simulacija; uplinjanje